Dialogical Community Classrooms Promoting Collective Motivations From the Diversity of Social Contexts - Astorga-Lineros, Blanca (2023)
Introduction. This research addresses three experiences of dialogic community classrooms working from the perspective of the Enlazando Mundos [Intertwining Worlds] dialogic pedagogy in Chile in different cultural contexts: rural, semi-rural and urban. It aims to identify the motivations activating the collective participation of social agents and their relationship with the modes of reciprocal recognition based on Honneth’s theory of justice. Method. It uses a participatory action research approach conducted through the kishu kimkelay ta che research-dialogical methodology (Ferrada, & Del Pino, 2018; Ferrada, 2017; Ferrada et al., 2014). The approach involves social agents, who participate in community classrooms, to form research communities to lead research processes, determining the problem to be investigated and the development of phases to be implemented. The construction of knowledge was achieved through the development of collective dialogues and dialogic conversations. Results. Three categories were identified. In them, synergies, the justification for participation, and the problems mobilizing transformation processes in each classroom were recognized; they were based on extrinsic, intrinsic, and transcendental motivational dimensions. Conclusions. The transcendental motivations are those that encourage the process of co-construction of own knowledge, from the full recognition between agents and cultural validation in each territory, establishing in each of the classrooms dynamics of justice from the identification of the spheres of recognition: love, equal treatment, and social esteem.